POPULAR BUSINESS AUTOMATION SOFTWARE IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the most popular business automation software used in Uzbekistan. It highlights how such programs simplify business processes like sales, inventory, accounting, and customer relations, thereby increasing efficiency. The paper analyzes the use and advantages of systems such as 1C, iScala, SAP, Zoho, MyTrade, and ORIF PRO in the Uzbek business environment.